2021
DOI: 10.3390/stresses1040018
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzyme Activities as Biomarkers of Cu and Pb Stress in Centella asiatica

Abstract: The present study investigated the antioxidant enzyme activities (AEA) of ascorbate peroxidase (APX), catalase (CAT), guaiacol peroxidase (GPX), and superoxide dismutase (SOD) as biomarkers of Cu and Pb stress by using Centella asiatica grown in an experimental hydroponic condition. The results showed (i) higher accumulations of Cu and Pb in the roots of C. asiatica than those in the leaves, (ii) synergistic effects of Cu and Pb stress at higher metal-level exposures, and (iii) Cu and Pb stress triggered the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Other researchers have also reported similar findings. Yap et al (2021) observed elevated antioxidant SOD in plants exposed to the metal copper. Benhamdi et al (2021) also reported results with similar trends to our findings.…”
Section: Discussionmentioning
confidence: 94%
“…Other researchers have also reported similar findings. Yap et al (2021) observed elevated antioxidant SOD in plants exposed to the metal copper. Benhamdi et al (2021) also reported results with similar trends to our findings.…”
Section: Discussionmentioning
confidence: 94%
“…These BSAF findings suggest that C. Obtusa shells accumulate more Cu and Cd from environmental sediments compared to soft tissues and shells. The discrepancy in results can be attributed to species digestion physiology and metal absorption rates [ 28 , 29 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, APX, CAT, and SOD enzymatic activities in roots were higher compared to activity in leaves. Similarly, a study with Centella asiatica plants subjected to Pb stress conditions showed higher activities of GPX, APX, and CAT in the roots than in the leaves [87]. The difference in enzyme activities between the leaf and the root may be due to the fact that the contaminant comes into natural contact with the radical system, and this system activates a rapid response as protection against oxidative stress [88].…”
Section: Impact Of As and Sio 2 Nps On Antioxidant Systemmentioning
confidence: 97%